Variation of Local Structure and Reactivity of Pt/C Catalyst for Accelerated Degradation Test of Polymer Electrolyte Fuel Cell Visualized by Operando 3D CT‐XAFS Imaging. Issue 4 (8th March 2022) - Matsui, Hirosuke; Ishiguro, Nozomu; Tan, Yuanyuan; Maejima, Naoyuki; Muramoto, Yuta; Uruga, Tomoya; Higashi, Kotaro; Nguyen, Duong‐Nguyen; Dam, Hieu‐Chi; Samjeské, Gabor; Tada, Mizuki
Abstract: In practical applications of polymer electrolyte fuel cells (PEFC), the wide variations of local structures and environment of electrocatalysts bring about complex reaction behaviours inside a membrane electrode assembly (MEA). The variations of local coordination structure and redox response of a Pt/C cathode catalyst in an MEA before and after a typical accelerated degradation test (ADT) were three‐dimensionally visualized by operando Pt LIII ‐edge computed‐tomography X‐ray absorption fine structure (CT‐XAFS) imaging under PEFC operating conditions for the first time. The set of operando CT‐XANES and CT‐EXAFS analyses visualized changes in the local coordination structure and redox reactivity of the Pt catalyst by a typical ADT process. Abstract : Operando CT‐XAFS imaging of an MEA with a Pt/C cathode catalyst before and after accelerated degradation test was reported under practical PEFC operating conditions. The full analysis of the CT‐XANES and CT‐EXAFS data provided the 3D images of local coordination structures which are key structural parameters for the reaction and degradation of the Pt cathode catalyst.